Pola Komunikasi Organisasi Languages Learning Club - Usereel Syahputra Oktova; Siti Nursanti; Fardiah Oktariani Lubis (Jurnal Ilmiah Wahana Pendidikan, 2023)
Research on "Language Learning Club Organizational Communication Patterns (Virtual Ethnographic Study of Languages ​​Learning Club Organizational Communication Patterns)" aims to study and analyze Languages ​​Learning Club organizational communication patterns. The theory used in this study is Mead's symbolic interaction theory concept in which there are three dimensional variables namely mind, self and society. The method used in this study is a descriptive qualitative research method using a virtual ethnographic analysis knife. The results of the research and discussion show that in the dimensions of the mind, organizational communication patterns of the Languages ​​Learning Club use two types of messages, namely two types of messages, namely persuasive and informative, while the dimensions of self do not run optimally due to the lack of participation from outsiders of the Languages ​​Learning Club and the variable dimensions of the community's communication patterns. organizations built by members of the Languages ​​Learning Club can give a positive color to the existence of the Languages ​​Learning Club